Wspomnienie roli, jaką odegrał profesor Władysław Kuraszkiewicz w początkowym okresie białorutenistycznych badań gwaroznawczych w Polsce - Smułkowa, Elżbieta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
Post-war research on Belarusian dialects in Poland using linguistic geography methods was launched in the 1950s by Prof. Antonina Obrębska-Jabłońska and her associates at the Polish-Soviet Institute in Warsaw. Before long, the institute’s Eastern Slavic sections were transferred to the Slavic Studies Unit of the Polish Academy of Sciences, where this work was continued. The main source of information on Eastern Slavic dialects between the Bug and Narew rivers, i.e. in the southern part of the area planned to be included in field studies, was Władysław Kuraszkiewicz’s article from 1939. In this work the Professor discussed the accentually determined development of Belarusian and Ukrainian diphthongs and the position-dependent depalatalization of consonants as well as mentioning preserved relics of infinitive forms of the it’`ie and peč`ye type, which in a subsequent work he explained as being a relic of the Jatzvingian (Yotvingian) language. The present paper highlights the merits of the distinguished Polish Slavic studies scholar, Professor Władysław Kuraszkiewicz, as a person, researcher and teacher.